House dust mite‐driven neutrophilic airway inflammation in mice with TNFAIP3‐deficient myeloid cells is IL‐17‐independent. Issue 12 (27th September 2018) - Vroman, Heleen; Das, Tridib; Bergen, Ingrid M.; van Hulst, Jennifer A. C.; Ahmadi, Fatemeh; van Loo, Geert; Lubberts, Erik; Hendriks, Rudi W.; Kool, Mirjam
Summary: Background: Asthma is a heterogeneous disease of the airways that involves several types of granulocytic inflammation. Recently, we have shown that the activation status of myeloid cells regulated by TNFAIP3/A20 is a crucial determinant of eosinophilic or neutrophilic airway inflammation. However, whether neutrophilic inflammation observed in this model is dependent on IL‐17 remains unknown. Objective: In this study, we investigated whether IL‐17RA‐signalling is essential for eosinophilic or neutrophilic inflammation in house dust mite (HDM)‐driven airway inflammation. Methods: Tnfaip3 fl/fl x Lyz2 +/cre ( Tnfaip3 LysM‐KO ) mice were crossed to Il17ra KO mice, generating Tnfaip3 LysM Il17ra KO mice and subjected to an HDM‐driven airway inflammation model. Results: Both eosinophilic and neutrophilic inflammation observed in HDM‐exposed WT and Tnfaip3 LysM‐KO mice respectively were unaltered in the absence of IL‐17RA. Production of IL‐5, IL‐13 and IFN‐γ by CD4 + T cells was similar between WT, Tnfaip3 LysM‐KO and Il17ra KO mice, whereas mucus‐producing cells in Tnfaip3 LysM‐KO Il17ra KO mice were reduced compared to controls. Strikingly, spontaneous accumulation of pulmonary Th1, Th17 and γδ‐17 T cells was observed in Tnfaip3 LysM‐KO Il17ra KO mice, but not in the other genotypes. Th17 cell‐associated cytokines such as GM‐CSF and IL‐22 were increased in the lungs of HDM‐exposed Tnfaip3 LysM‐KO Il17ra KO mice, compared to IL‐17RA‐sufficient controls. Moreover, neutrophilic chemo‐attractants CXCL1, CXCL2, CXCL12 and Th17‐promoting cytokines IL‐1β and IL‐6 were unaltered between Tnfaip3 LysM‐KO and Tnfaip3 LysM‐KO Il17ra KO mice. Conclusion and Clinical Relevance: These findings show that neutrophilic airway inflammation induced by activated TNFAIP3/A20‐deficient myeloid cells can develop in the absence of IL‐17RA‐signalling. Neutrophilic inflammation is likely maintained by similar quantities of pro‐inflammatory cytokines IL‐1β and IL‐6 that can, independently of IL‐17‐signalling, induce the expression of neutrophil chemo‐attractants.